Perbedaan Mindful Parenting di Malaysia dan Indonesia : Differences in Mindful Parenting in Malaysia and Indonesia - Mega Ratrisari; Arri Handayani; Agus Setyawan (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Mindful parenting is a parenting approach that emphasizes mindfulness and attention when interacting with children. This approach aims to improve the quality of the relationship between parents and children and reduce stress in parenting. This study explores mindful parenting from a cultural and social perspective in both countries with different cultural backgrounds and values. This study aims to identify and analyze differences in the implementation of mindful parenting between Malaysia and Indonesia. This study used a quantitative survey method, collecting data from many parents in Malaysia and Indonesia. The questionnaire used in this study was designed to measure various aspects of mindful parenting, including parental self-awareness, mindfulness in the present moment, and the ability to manage emotions in parenting situations. The data collected were analyzed using statistical techniques to identify significant differences in implementing mindful parenting in both countries. The results showed variations in how parents in Malaysia and Indonesia implemented the principles of mindful parenting. Cultural factors, social norms, and traditional parenting practices influenced the implementation of mindful parenting in each country. These findings provide important insights for practitioners, researchers, and policymakers in developing more effective and culturally appropriate mindful parenting training programs. Thus, this study contributes to a deeper understanding of mindful parenting and its implications in child rearing in Malaysia and Indonesia.